Scaling Point‐Scale (Pedo)transfer Functions to Seamless Large‐Domain Parameter Estimates for High‐Resolution Distributed Hydrologic Modeling: An Example for the Rhine River - Imhoff, R. O.; van Verseveld, W. J.; van Osnabrugge, B.; Weerts, A. H. (Water resources research, 2020)
Moving toward high‐resolution gridded hydrologic models asks for novel parametrization approaches. A high‐resolution conceptual hydrologic model (wflow_sbm) was parameterized for the Rhine basin in Europe based on point‐scale (pedo)transfer functions, without further calibration of effective model parameters on discharge. Parameters were estimated on the data resolution, followed by upscaling of parameter fields to the model resolution. The method was tested using a 6‐hourly time step at four model resolutions (1.2, 2.4, 3.6, and 4.8 km), followed by a validation with discharge observations and a comparison with actual evapotranspiration (ETact) estimates from an independent model (DMET Land Surface Analysis Satellite Application Facility). Additionally, the scalability of parameter fields and simulated fluxes was tested. Validation of simulated discharges yielded Kling‐Gupta Efficiency (KGE) values ranging from 0.6 to 0.9, except for the Alps where a volume bias caused lower performance. Catchment‐averaged temporal ETact dynamics were comparable with independent ET estimates (KGE ≈ 0.7), although wflow_sbm model simulations were on average 115 mm yr−1 higher. Spatially, the two models were less in agreement (SPAEF = 0.10), especially around the Rhine valley. Consistent parameter fields were obtained, and by running the model at the different resolutions, preserved ETact fluxes were found across the scales. For recharge, fluxes were less consistent with relative errors around 30% for regions with high drainage densities. However, catchment‐averaged fluxes were better preserved. Routed discharge in headwaters was not consistent across scales, although simulations for the main Rhine River were. Better processing (scale independent) of the river and drainage network may overcome this issue. Plain Language Summary Hydrologic models are used for flood and drought predictions. Most models have parameters, and to increase model performance, hydrologists often tune these parameters by calibration. State‐of‐the‐art gridded hydrologic models have parameter sets per grid cell, leading to many parameters and making current calibration procedures far from ideal. Here, we tested the use of well‐known (pedo)transfer functions from literature to estimate these parameter values, something which can reduce the calibration burden. By using parameter‐specific upscaling rules to derive seamless parameter maps for the wflow_sbm model, which explicitly takes subsurface lateral flows into account, this gives a model which is scalable to different grid cell sizes. We assessed the approach on multiple model resolutions, and we found consistent parameter fields and the preservation of vertical fluxes. Only routed discharge, a key output, deteriorates for headwater catchments on coarser resolutions. We attribute this to model structure and the derivation procedure of the river network on different scales, resulting in the loss of lateral flow representation on coarser resolutions. Nevertheless, discharge and evapotranspiration simulations are similar to observations and other models. Hence, regionalization with literature transfer functions and upscaling techniques can further lower the calibration burden and enable predictions in ungauged basins. Key Points Seamless distributed parameter maps can be obtained for the gridded hydrologic model wflow_sbm with transfer functions from literature Application of wflow_sbm with these seamless parameter maps yields simulation results with high KGE and NSE across the Rhine basin Fluxes matched across model scales for evapotranspiration, but this match was considerably less for fluxes affected by (sub)surface flows